1979
DOI: 10.1007/bf02533580
|View full text |Cite
|
Sign up to set email alerts
|

HDL‐cholesterol levels in the multiple risk factor intervention trial (MRFIT) by the MRFIT Research Group

Abstract: Preliminary data from the Multiple Risk Factor Intervention Trial (MRFIT) have been examined for evidence that the program has an influence on plasma HDL-cholesterol. The overall mean level of this lipoprotein in the initial cohort of 1,084 men was not altered by two years of participation in this risk factor reduction project. However, changes did occur, both upwards and downwards, in some individuals. There were significant negative associations between change in HDL-cholesterol and changes in body mass, VLD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…Multivariate analysis demonstrated that the Taql B polymorphism had an effect on HDL cholesterol and HDL 2 that was independent of age, sex, body mass index, oral contraceptive use, exercise, alcohol consumption, and plasma triglycerides. In smokers, the presence of the B2B2 genotype did not result in increased HDL cholesterol or HDL 2 , whereas in obese subjects, the difference between B1B1 and B2B2 individuals was diminished. We conclude that the Taql B RFLP is associated with a quantitatively significant effect on plasma HDL 2 levels that is independent of plasma triglycerides and interacts with lifestyle factors.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Multivariate analysis demonstrated that the Taql B polymorphism had an effect on HDL cholesterol and HDL 2 that was independent of age, sex, body mass index, oral contraceptive use, exercise, alcohol consumption, and plasma triglycerides. In smokers, the presence of the B2B2 genotype did not result in increased HDL cholesterol or HDL 2 , whereas in obese subjects, the difference between B1B1 and B2B2 individuals was diminished. We conclude that the Taql B RFLP is associated with a quantitatively significant effect on plasma HDL 2 levels that is independent of plasma triglycerides and interacts with lifestyle factors.…”
mentioning
confidence: 80%
“…4 The strong inverse correlation between triglyceride concentration and HDL concentration 5 and HDL size in normal individuals 6 is thought to be due to triglyceride transfer from very-low-density lipoprotein (VLDL) and chylomicrons to HDL, with subsequent the association, since it did not differ between genotype groups and was not correlated with HDL 2 concentration. Multivariate analysis demonstrated that the Taql B polymorphism had an effect on HDL cholesterol and HDL 2 that was independent of age, sex, body mass index, oral contraceptive use, exercise, alcohol consumption, and plasma triglycerides.…”
mentioning
confidence: 99%
“…In a recent report from the Multiple Risk Factor Intervention Trial, a decrease in serum thiocyanate levels, an objective biochemical measure of cigarette smoking habits,'7 was associated with a small increase in HDL-C. 31 In the Israeli study of adult men, cigarette smokers had higher total cholesterol with lower alipoprotein cholesterol, implying higher P-lipoprotein cholesterol. '0 The number of cigarettes smoked per day and the duration of the use of tobacco were associated with an increase in triglycerides for men in a study of 9,000 presumably healthy persons in France.5 In a study of 2,568 men in Great Britain, increased cigarette smoking was shown to be related to a decrease in HDL-C. 8 Since cigarette smoking and oral contraceptive use often occur together in young women, it is important to observe the interaction of these with the other risk factor variables.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking has been shown to adversely effect HDL-cholesterol. 49 Some studies with high fibre diets have suggested significant improvement in plasma triglyceride levels and in HDL/LDL cholesterol ratio. 50,51 Dietary rape seed oil, margarine rich in sitostanol ester was effective for lowering VLDL and LDL cholesterol and increasing HDL-cholesterol in hypercholesterolaemic non-insulin-dependent diabetic subjects.…”
Section: Resultsmentioning
confidence: 99%